Elucidating the mechanisms and developing mitigation strategies of mineral scaling in membrane desalination - Yin, Yiming, author; Tong, Tiezheng, advisor; Sharvelle, Sybil, committee member; Carlson, Kenneth, committee member; Li, Yan, committee member (Colorado State University. Libraries, 2022)
Mineral scaling in membrane desalination, which is referred to as the accumulation of minerals on the membrane surface, has been considered as the primary constraint that limits the water recovery and efficiency of membrane desalination significantly. The occurrence of mineral scaling results in the decrease of water flux and compromises the lifetime of membrane materials, leading to increased needs of energy consumption and facility maintenance. Furthermore, the limited water recovery of membrane desalination due to mineral scaling also results in the production of high volumes of concentrated brines, which may require thermal-based technologies to further reduce the brine volume to achieve minimal liquid discharge (MLD) or zero liquid discharge (ZLD). However, these technologies are energy- and cost-intensive. Therefore, developing feasible and effective strategies to mitigate mineral scaling in membrane desalination is urgently needed to improve the resilience and performance of desalination systems, which will ultimately facilitate the implementation of desalination to mitigate global water scarcity and reduce the environmental risks and cost associated with brine management. Gaining a fundamental understanding of mineral scaling mechanisms and the relationship between scaling behaviors and membrane surface properties are the key prerequisites to the rational design of scaling mitigation strategies in membrane desalination. First, I dedicated efforts to elucidate the scaling mechanism of silica in membrane distillation (MD), a hybrid thermal-membrane desalination technology. Three PVDF membranes with different surface wettability were used to unveil underlying scaling mechanisms of silica in MD. The experimental results revealed that homogeneous nucleation played an important role in inducing silica scaling in MD, while heterogeneous nucleation facilitated the formation of silica scaling layer on the membrane surface. Additionally, I demonstrated that tuning membrane surface wettability was insufficient to reduce silica scaling in MD. Next, I investigated the effect of membrane surface wettability on the scaling kinetics and reversibility of gypsum scaling and silica scaling in MD. Unlike the formation of silica that is regulated by polymerization reactions, the formation of gypsum is governed by crystallization reactions between Ca2+ and SO42- ions. In this work, I demonstrated that superhydrophobic membrane was able to delay the induction time of gypsum scaling and enhanced scaling reversibility, which resulted in increased total water recovery. However, this strategy was not effective to mitigate silica scaling. Such distinct experimental observations between gypsum scaling and silica scaling were attributed to their different formation mechanisms and corresponding interactions with membrane surfaces. Further, in addition to the development of novel membrane materials to resist scaling, the use of anti-scalants to mitigate gypsum scaling and silica scaling was also explored in MD. Although the use of anti-scalants has been widely adopted in the industry, the effectiveness of anti-scalants and the underlying factors that control the anti-scaling efficiency have not been systematically studied. Three anti-scalants with different functional groups were used to elucidate the efficiencies of anti-scalants in mitigating gypsum scaling and silica scaling in MD. Poly(acrylic) acid and poly(ethylenimine), which were enriched with carboxyl and amino groups, were shown to be effective to inhibit gypsum scaling and silica scaling, respectively. The mitigating effect of poly(acrylic) acid molecules on gypsum scaling was due to their effects of stabilizing scaling precursors, whereas poly(ethylenimine) facilitated silica polymerization and altered the morphology of silica scale layer on the membrane surface. This work indicates that anti-scalants with different functional groups are needed for different mineral scaling types. Finally, I compared the efficiencies of membrane surface modification and anti-scalants in mitigating mineral scaling in membrane desalination. The efficiencies of four types of membrane surface modification in mitigating gypsum scaling in reverse osmosis (RO) were compared with the use of anti-scalant poly(acrylic) acid. It was shown that membrane surface modification was only able to reduce the water flux decline caused by gypsum scaling moderately, whereas the use of anti-scalants greatly inhibited gypsum scaling. In addition, I also demonstrated that the use of anti-scalants was highly efficient in preventing gypsum scaling in a combined RO-MD treatment train, which dramatically increased the total water recovery. Therefore, a comparative insight on the efficiencies of different scaling mitigation strategies was provided, which has the potential to guide the selection of the most appropriate strategy to mitigate mineral scaling in membrane desalination.
Keywords: mineral scaling; membrane desalination